Ceiling fans in commercial buildings: In situ airspeeds & practitioner experience. (January 2019) - Present, Elaina; Raftery, Paul; Brager, Gail; Graham, Lindsay T.
Abstract: Ceiling fans are a traditional approach for increasing occupant comfort and are well-established in residential application in many parts of the world. However, they are infrequently included in commercial spaces even though they have the potential to bring benefits including increased occupant comfort and decreased energy use either through raised setpoints in cooling or destratification in heating. This study provides practical insights into the case of ceiling fans in commercial spaces. We conducted 13 interviews with architects, engineers, and facilities managers from California and around the country to compile common themes of experience. These professionals provided lessons learned from 20 operational projects that include ceiling fans serving a wide set of functions in commercial spaces. Understanding the challenges they faced and the lessons they learned from these projects will facilitate prioritization of research and communication efforts. We also took in situ airspeed measurements at five of the projects to provide insight into real-world conditions in commercial buildings with ceiling fans. For these, the ceiling fans' operation results in generally relatively low airspeeds, often under 0.2 m/s. We also found just 25% of the 20 projects discussed by interviewees had any type of automation in the ceiling fan controls. This study serves as a resource for designers and for the wider industry, to frame a path forward for the inclusion of ceiling fans in commercial buildings. Highlights: Took 65 measurements in 5 buildings with ceiling fans, interviewed 13 professionals. Designers specified ceiling fans for cooling, destratification and other IEQ benefits. Summarized best practices, uncertainties, and barriers to designing with ceiling fans. Median encountered airspeed was 0.15 m/s, below ASHRAE 55 elevated airspeed threshold. Zone temperatures and cooling setpoints suggested unrealized energy savings potential.